Infiltrations into Wireless Networks by Attackers - Haroon Rashid Hammood Al Dallal; Yasir Adil Mukhlif (Genius Journals, 2022)
Due to the insecurity of wireless channels, communications are open to a wide variety of different sorts of assaults. It is still difficult and important to solve the problem of communications in wireless networks. In this study, current developments It presents the requirements and capabilities necessary for encrypting data carried out via "wireless networks". "Wireless networks" are now being utilized in a broad variety of commercial and military applications to collect data in real-time and dependent on occurrences. The nature of network deployment renders them susceptible to a variety of security risks. Traditional security techniques are insufficient to ensure the safety of the nodes because of the constraints placed on available resources. The study of many aspects of network security has led to the development of several preventative measures. Throughout this article, we have looked at several security techniques. We created and analyzed strong model for the integration of heterogeneous wireless networks by using different security techniques in terms of the overheads associated with the packets and compared the amount of time it took to send the packets, the average amount of delay, and the amount of energy used. That result shows that the transmission outgoings were reduced as compared to other techniques, and this is demonstrated by the reduced costs.
Keywords: demonstrated; techniques; preventative; safety